Grindr Users Take More Risks, but Are More Open to Human Immunodeficiency Virus (HIV) Pre-exposure Prophylaxis: Could This Dating App Provide a Platform for HIV Prevention Outreach?. (2nd November 2019) - Hoenigl, Martin; Little, Susan J; Grelotti, David; Skaathun, Britt; Wagner, Gabriel A; Weibel, Nadir; Stockman, Jamila K; Smith, Davey M
Abstract: Background: Technology has changed the way that men who have sex with men (MSM) seek sex. More than 60% of MSM in the United States use the internet and/or smartphone-based geospatial networking apps to find sex partners. We correlated use of the most popular app (Grindr) with sexual risk and prevention behavior among MSM. Methods: A nested cohort study was conducted between September 2018 and June 2019 among MSM receiving community-based human immunodeficiency virus (HIV) and sexually transmitted infection (STI) screening in central San Diego. During the testing encounter, participants were surveyed for demographics, substance use, risk behavior (previous 3 months), HIV pre-exposure prophylaxis (PrEP) use, and Grindr usage. Participants who tested negative for HIV and who were not on PrEP were offered immediate PrEP. Results: The study included 1256 MSM, 1090 of whom (86.8%) were not taking PrEP. Overall, 580 of 1256 (46%) participants indicated that they used Grindr in the previous 7 days. Grindr users reported significantly higher risk behavior (greater number of male partners and condomless sex) and were more likely to test positive for chlamydia or gonorrhea (8.6% vs 4.7% of nonusers; P = .005). Grindr users were also more likely to be on PrEP (18.7% vs 8.7% of nonusers; P < .001) and had fewer newly diagnosed HIV infections (9 vs 26 among nonusers; P = .014). Grindr users were also nearly twice as likely as nonusers to initiate PrEP (24.6% vs 14%; P < .001). Conclusions: Given the higher risk behavior and greater acceptance of PrEP among MSM who used Grindr, Grindr may provide a useful platform to promote HIV and STI testing and increase PrEP uptake. Abstract : Grindr users took more sexual risks than those who did not use the app. However, Grindr users were also more likely to use, or be open to using, HIV pre-exposure prophylaxis, suggesting the app could be a platform to encourage HIV prevention.